HASIL BELAJAR KOGNITIF IPA FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERMAIN JAWABAN PADA MATERI PEMUAIAN DI SEKOLAH MENENGAH PERTAMA - Apriani, Delta; ', Azhar; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to describe the cognitive learning science through the cognitive learning outcames of physics science through the implementation of playing answer cooperative learning model on the expantion matter in junior high school. The type of research is quasi-experimental, with a comparison group design intact. The sample in this study is VII.3 class with 36 students is class which in implementation with playing answer cooperative learning model, and VII.4 class with 36 students that conventional learning classes. The data in this study were analyzed descriptively. Based on the result of cognitive learning of students in the class implementation of cooperative learning to play the answers are in the good category with persentse 75.37%, whereas in the conventional classroom learning cognitive the category quite well with the percentage of 66.48%. It can be concluded that science teaching physics with cooperative learning to play the answers can improve cognitive achievement of students in the material expansion in SMPN 34 Pekanbaru.Keywords: Learning Outcomes, Cooperative Play Answers, Swelling